1999
DOI: 10.1097/00006676-199907000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lymphocyte Activation Modulates the Severity of Diet-Induced Acute Pancreatitis in Mice

Abstract: To examine the role of lymphocyte activation in the development of local and systemic complications in acute pancreatitis, we compared disease severity of choline-deficient, 0.5% ethionine supplemented (CDE) diet-induced acute pancreatitis in T-and B-cell deficient SCID mice and immunocompetent C.B-17 mice. Twenty-five female SCID and 17 female C.B-17 mice were fasted for 24 h and fed a CDE diet for 72 h. Twenty SCID and 12 C.B-17 mice were bled and their organs removed for histologic evaluation. Five control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 14 publications
(16 reference statements)
2
17
0
Order By: Relevance
“…However, in a previous study [15], we reported that, during acute pancreatitis, in the patients with the highest values of CRP, the increase in serum levels of the soluble IL-2 receptor -considered a marker of lymphocyte activation and distant complications [27] peaked later, lasted longer, and was higher than in the patients with normal CRP values. The results of this report are in agreement with our present findings of sustained, moderately high levels of peripheral blood mononuclear cell apoptosis in patients with complicated acute pancreatitis, when lymphocyte activation is to be presumed, in parallel with the degree of the complications, overwhelming peripheral blood mononuclear cell apoptosis, even activated.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, in a previous study [15], we reported that, during acute pancreatitis, in the patients with the highest values of CRP, the increase in serum levels of the soluble IL-2 receptor -considered a marker of lymphocyte activation and distant complications [27] peaked later, lasted longer, and was higher than in the patients with normal CRP values. The results of this report are in agreement with our present findings of sustained, moderately high levels of peripheral blood mononuclear cell apoptosis in patients with complicated acute pancreatitis, when lymphocyte activation is to be presumed, in parallel with the degree of the complications, overwhelming peripheral blood mononuclear cell apoptosis, even activated.…”
Section: Discussionmentioning
confidence: 74%
“…Induction of apoptosis in pancreatic acinar cells reduces the severity of experimental acute pancreatitis [17,[23][24][25]; besides, the resolution of the inflammatory responses developing in acute pancreatitis is dependent on neutrophil apoptosis which seems to be delayed during the illness [26]. Further, mortality rate and pulmonary injury are reduced in T-and B-cell-deficient mice with diet-induced acute pancreatitis [27], and depletion of circulating CD3+ lymphocytes has been found to reduce systemic complications in experimental pancreatitis [28]. Thus, systemic leucocyte activation or inactivation can modulate the severity of acute pancreatitis [19,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-quantitative scoring of bleeding, edema, and inflammation of lung tissues was performed under high magnification (×400), using the Mayor and Osman score standard. 34,35 Assessment of hAMSC Localization in Lungs Lung tissues were harvested and fixed in 10% neutral buffer formalin. Immunohistochemical staining was performed as previously described.…”
Section: Assessment Of Lung Injurymentioning
confidence: 99%
“…As one can expect, several studies aimed at targeting specific leukocyte subsets such as neutrophils [6,7,8,9], lymphocytes [10,11], or monocytes [12,13,14] and indeed demonstrated a significant improvement of pancreatic damage and mortality in various experimental pancreatitis models. However, a clinical translation of these achievements has yet to take place.…”
Section: Introductionmentioning
confidence: 99%